Designerly Ways of Knowing in HCI Education: A Case Study of a Peer Community-Based Studio - Gamboa, Mafalda; Ljungblad, Sara (Frontiers in Computer Science, 2022)
Design methods and approaches are common within Human-Computer Interaction. And while design is recognised as a discipline with its own epistemology and pedagogy outside of HCI, there is a lot of work to be done in incorporating, facilitating, and developing designerly knowledge in HCI education. The abrupt shift towards distance education caused by COVID-19 surfaced the necessity for course design to purposely support online informal learning environments and facilitating tacit knowledge as previously prevalent in the design studio environment. Firstly, we present theory on design epistemology, related to "designerly ways of knowing" and the role of the studio in the learning process. Secondly, a case study presents the set up of a digital studio for a course in Designing User Experiences, with an emphasis on supporting a community-based studio. The empirical material includes an overview of the course set up and a thorough qualitative analysis of the feedback provided by a cohort of 48 students with diverse backgrounds. The course was conducted online and heavily based on the use of software such as Zoom and Miro. We conclude by offering a set of themes in three categories to be considered when designing community-based ``designerly'' courses within HCI. As future work, we suggest the Community-Based Designerly Scale to be used, adapted, and developed by teachers and students as a tool in their educational practice.